MAD—microbial (origin of) Alzheimer’s disease hypothesis: from infection and the antimicrobial response to disruption of key copper-based systems - Min, Jin-Hong; Sarlus, Heela; Harris, Robert A. (Frontiers in Neuroscience, 2024)
Microbes have been suspected to cause Alzheimer’s disease since at least 1908, but this has generally remained unpopular in comparison to the amyloid hypothesis and the dominance of Aβ and Tau. However, evidence has been accumulating to suggest that these earlier theories are but a manifestation of a common cause that can trigger and interact with all the major molecular players recognized in AD. Aβ, Tau and ApoE, in particular appear to be molecules with normal homeostatic functions but also with alternative antimicrobial functions. Their alternative functions confer the non-immune specialized neuron with some innate intracellular defenses that appear to be re-appropriated from their normal functions in times of need. Indeed, signs of infection of the neurons by biofilm-forming microbial colonies, in synergy with herpes viruses, are evident from the clinical and preclinical studies we discuss. Furthermore, we attempt to provide a mechanistic understanding of the AD landscape by discussing the antimicrobial effect of Aβ, Tau and ApoE and Lactoferrin in AD, and a possible mechanistic link with deficiency of vital copper-based systems. In particular, we focus on mitochondrial oxidative respiration via complex 4 and ceruloplasmin for iron homeostasis, and how this is similar and possibly central to neurodegenerative diseases in general. In the case of AD, we provide evidence for the microbial Alzheimer’s disease (MAD) theory, namely that AD could in fact be caused by a long-term microbial exposure or even long-term infection of the neurons themselves that results in a costly prolonged antimicrobial response that disrupts copper-based systems that govern neurotransmission, iron homeostasis and respiration. Finally, we discuss potential treatment modalities based on this holistic understanding of AD that incorporates the many separate and seemingly conflicting theories. If the MAD theory is correct, then the reduction of microbial exposure through use of broad antimicrobial and anti-inflammatory treatments could potentially alleviate AD although this requires further clinical investigation.